Diagnostic Performance of Procalcitonin and C-Reactive Protein in Pediatric Acute Pyelonephritis: A Hospitalbased Study - Jahan, Ishrat; Jesmin, Tahmina; Saha, Sudipta; Khatun, Sufia; Ashraf, Rezwana; Rahman, Azizur; Rahman, Shorna; Mamun, Abdullah Al; Muin Uddin, Golam (Journal of Pediatric Nephrology, 2022)
Background and Aim: Urinary Tract Infection (UTI) is a common bacterial infection in children causing permanent renal damage. Differentiation between Acute Pyelonephritis (APN) and lower UTI is vital due to the involvement of renal parenchyma in APN. This study aimed to assess the efficiency of Procalcitonin (PCT) with C-Reactive Protein (CRP) to predict APN in children with UTI in a tertiary care hospital. Methods: This analytical cross-sectional study was conducted in a tertiary care hospital between March 2013 and July 2014. Children aged 1 month to 16 years with febrile UTI were included in the study Sensitivity, specificity, positive predictive value, negative predictive value, and receiver operating characteristic (ROC) curve were used to assess quantitative variables for diagnosing APN. Results: The Mean±SD age values in the APN group were 73.11±52.29 months, while it was 76.25±47.23 months in the lower UTI group. The Area Under the Curve (AUC) for fever, White Blood Cell (WBC), CRP, and PCT of the respondent showed that CRP was at the cut-off point of 5.0 mg/L, resulting in a sensitivity of 82.4% and a specificity of 80.0%, respectively. PCT was at the cut-off point of 1300 pg/mL, resulting in a sensitivity of 76.5% and a specificity of 100.0%, respectively. By comparing the Receiver Operating Characteristic (ROC) curve, PCT had a significantly higher Area Under the Curve (AUC) than CRP for differentiating APN and lower UTI. Conclusion: Serum CRP and PCT are good markers for diagnosing APN in febrile UTI in children. However, the study showed that PCT is a better marker to differentiate APN and lower UTI compare to CRP.